Integration of E-Learning Platforms in Moroccan Higher Education: Assessing the Technological Leap and Addressing the Digital Divide Among Urban and Rural Students - Ahmed El Ghazali; Leila Benbrahim (Research and Advances in Education, 2024)
The integration of e-learning platforms in Moroccan higher education has been a significant step towards modernizing the educational landscape. This study examines the adoption and impact of e-learning platforms in Moroccan universities, with a particular focus on the technological and socio-economic disparities between urban and rural areas. The research analyzes the availability and quality of internet connectivity and digital devices, as well as the challenges and barriers faced by students and educators. Additionally, the study explores the impact of e-learning on student engagement and academic performance, providing a comparative analysis before and after the integration of these platforms. The findings highlight the need for targeted interventions to bridge the digital divide and ensure equitable access to e-learning resources. Recommendations for improving digital infrastructure, providing financial support, and enhancing digital literacy are discussed to promote effective and inclusive e-learning in Morocco.